Apoptosis and turnover disruption of olfactory sensory neurons in eosinophilic chronic rhinosinusitis - Chen, Yuetong; Li, Minghan; Lu, Juan (Frontiers in Cellular Neuroscience, 2024)
Olfactory dysfunction (OD) is one of the important and difficult-to-treat symptoms of eosinophilic chronic rhinosinusitis (CRS), which is typically associated with type 2 inflammation where eosinophils (EOSs) function as both effectors and initiators. Eosinophilic infiltration in the olfactory mucosa (OM) is associated with severe OD, mucosal erosion, and more loss of olfactory sensory neurons (OSNs). Active EOS-derived cytokines, chemokines, and eosinophil granule proteins may lead to aggravation of inflammation, tissue damage, and impairment of the survival and regeneration of OSNs. Recent studies show that EOSs can lead to apoptosis of OSNs through axonal and neural body damage, turnover disorder of OSNs through the loss of immature OSNs and globose basal cells (GBCs), changed proliferative activity of horizontal basal cells (HBCs), and dysfunction of OSNs through the breakdown of neuroepithelial integrity and alteration of ion concentration in OSNs and mucin. In this review, we outline the current progress on the role of EOSs on OD in patients with eosinophilic CRS and the mechanism of EOS-associated injury of the OM and OSNs in experimental animal models with sinonasal inflammation. Further investigations on the molecular mechanisms of tissue eosinophilia-induced injury of OSNs are warranted to obtain new therapeutic targets and achieve better restoration of olfactory function.